THE PRINCIPLES OF EQUIVALENCE, VERSATILITY, OPENNESS, AND COOPERATION AS BASIC COMPONENTS OF THE DEMOCRATIZATION OF SCIENCE - Kubalskyi, Oleh (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. In the minds of socially turbulent global trends, the problems of democratization of all spheres of sustainable life are gaining new relevance and significance. In this context, especially the role played by the nutrition of the democratization of science in its epistemic, procedural, and collective manifestations. The article details the conceptual and theoretical analysis of the basic principles of the democratization of modern science, namely of equanimity, cooperation, diversity and openness. The aim of the research is to identify the interrelationship of the principles of equal opportunities, cooperation, diversity, and openness as principles of democratization of science. Research methodology. The democratization of science is carried out on the basis of the tradition of the philosophy of pragmatism, in particular, presented in the philosophical methodology developed by John Dewey and Richard Rorty. Of particular importance is the clear correlation of a person’s behavior with the principles of activity established by him in accordance with basic values. In the field of science, these are academic values, in particular, the scientist’s ethos, which was classically analyzed by the American science theorist Robert Merton. Research results. It is said that the democratization of science is based on the principles of equal possibilities, cooperation, versatility, and openness. The principle of equal opportunities is especially important in the context of the security of gender equality and the defense of the other categories of citizens in the face of discrimination, as well as for the security of scientific communication, which is based on the recognition of freedom and equal partnership. Discussion. The principle of diversity, orientation towards new ideas and alternative points of dawn, reveals the open space for the new. The principle of openness, which is based on the knowledge of the fact that no one can have a monopoly on the truth, characterizes the right of a free choice of directly scientific results, the approval of critical thought, honesty and publicity of science. Conclusions. Freedom to choose the subject of scientific research is the achievement of a free political system, as it is guilty of protecting it for the sake of diversity and creativity. At the same time, the beginnings of the freedom of science achieve the development of science and of innovations.